2010
DOI: 10.1074/jbc.m110.134585
|View full text |Cite
|
Sign up to set email alerts
|

Pgrmc1 (Progesterone Receptor Membrane Component 1) Associates with Epidermal Growth Factor Receptor and Regulates Erlotinib Sensitivity

Abstract: Tumorigenesis requires the concerted action of multiple pathways, including pathways that stimulate proliferation and metabolism. Epidermal growth factor receptor (EGFR) is a transmembrane receptor-tyrosine kinase that is associated with cancer progression, and the EGFR inhibitors erlotinib/tarceva and tyrphostin/AG-1478 are potent anti-cancer therapeutics. Pgrmc1 (progesterone receptor membrane component 1) is a cytochrome b 5 -related protein that is up-regulated in tumors and promotes cancer growth. Pgrmc1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 56 publications
5
132
0
2
Order By: Relevance
“…Results of subsequent studies have indicated that AG205 binds to PGRMC1 and has a similar effect to that observed after treatment with Pgmrc1 siRNA in lung cancer cells, decreasing phosphorylation of ERK (Ahmed et al 2010b). Treatment with AG205 also decreases EGFR-dependent signaling in lung cancer cells, consistent with the proposed role of PGRMC1 as a binding partner with EGFR (Ahmed et al 2010a). Thus, AG205 is a useful PGRMC1 antagonist for exploring its adaptor protein functions.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Results of subsequent studies have indicated that AG205 binds to PGRMC1 and has a similar effect to that observed after treatment with Pgmrc1 siRNA in lung cancer cells, decreasing phosphorylation of ERK (Ahmed et al 2010b). Treatment with AG205 also decreases EGFR-dependent signaling in lung cancer cells, consistent with the proposed role of PGRMC1 as a binding partner with EGFR (Ahmed et al 2010a). Thus, AG205 is a useful PGRMC1 antagonist for exploring its adaptor protein functions.…”
Section: Introductionsupporting
confidence: 56%
“…Results from a recent study by Thomas et al (2014) indicating that PGRMC1 co-immunoprecipitates with membrane progesterone receptor alpha (mPRa) in several breast cancer cell lines and enhances its expression and function on the plasma membrane, and also enhances the membrane expression of estrogen receptor beta (ERb), further support a role of PGRMC1 as an adaptor protein and suggests that it has an important function in regulating the cell-surface expression and membrane receptor functions of steroid receptors. Results described in a recent report by Ahmed et al (2010a) which revealed that PGRMC1 associates with epidermal growth factor receptor (EGFR) and maintains EGFR at the plasma membrane indicate that PGRMC1 also acts as an adaptor protein for EGFR. This finding is likely to have broad implications for tumorigenesis because over-expression of EGFR in cancer cells is highly correlated with malignancy (Ono & Kuwano 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PGRMC1 has been shown to interact with EGFR and increase plasma membrane EGFR levels. 70 Accordingly, PGRMC1 expression increases in vitro breast cancer cell proliferation in the presence of growth factors and medroxyprogesterone acetate. 17 A link between PGRMC1 and EGFR has also been identified in zebrafish oocytes as a component of estrogen-induced meiotic arrest.…”
Section: Discussionmentioning
confidence: 99%
“…PGRMC1 has been shown to function as an adaptor protein for mPR␣, closely associating with it and regulating its expression and functions on the cell membrane (64). PGRMC1 likely influences multiple receptor functions in HUVECs because it also regulates the expression of EGFR and ER␤ on the membranes of human cells (1,64). Finally, the fact that coincubation with a nuclear estrogen receptor antagonist, ICI 182,780, did not modulate the NO response to the progestin treatments suggests that their effects are not mediated through a nuclear estrogen receptor-dependent pathway.…”
Section: E908 Mpr␣ Mediates P4 Upregulation Of No Synthesismentioning
confidence: 99%